Agricultura familiar, multifuncionalidade da agricultura e ruralidade: interfaces de uma realidade complexa - Leite de Camargo, Regina Aparecida [UNESP]; Aier de Oliveira, Julieta Teresa (Universidade Federal de Santa Maria (UFSM), 2012)
The last decades witnessed the revitalization of the debate around family farming with the addition of discussions regarding the multiple functions of agriculture, given the fact that rural areas are longer devoted exclusively to agricultural activities. In the Brazilian context, we believed that this debate must be permeated by analyses of how differentiated processes of land distribution and economic development, and the resulting types of agriculture, generate specific ruralities with characteristics such as, in the case of family farming, the maintenance of social and work practices marked by the relations among relatives and neighbours. It is in this light that this research analyses family agriculture in a rural area of Ouro Fino-MG, its historical heritage, and its participation in the creation of a physical and human landscape that greatly contributes to the attractiveness of the region.

Nas últimas décadas, assistimos à revitalização do debate em torno da agricultura familiar pela incorporação das discussões sobre as múltiplas funções da agricultura num rural que não pode mais ser visto como domínio exclusivo da atividade agrícola e dos agricultores. No contexto brasileiro, acreditamos que essa discussão deva ser permeada pela análise de como processos diferenciados de distribuição fundiária e desenvolvimento econômico e o tipo de agricultura resultante geram ruralidades específicas com características como, no caso da agricultura familiar, a manutenção de práticas sociais e de trabalho marcadas pelas relações de parentesco e vizinhança presentes numa sociedade de interconhecimento. Partindo desse princípio, este trabalho analisa a agricultura familiar de um bairro rural do município de Ouro Fino - MG, sua herança histórica e sua participação na criação de uma paisagem natural e humana que muito contribui para a atratividade da região.
Family farming, multifunctionality of agriculture and rurality. Interfaces of a complex reality
Keywords: peasant heritage; productive systems; rural landscapes; rural neighbourhoods